Photographic practices and transgressive aesthetics in Éric-Emmanuel Schmitt’s novel When I was a work of art (Philology, 2019)
In his novel When I Was a Work of Art Éric-Emmanuel Schmitt introduces the readers to the world of contemporary art from the character’s viewpoint. The character and narrator, Tazio Firelli, describes in a retrospective first-person narrative his own physical transformation from a young man into the “living sculpture” called Adam bis.The paper’s purpose is to analyse the photographic images in relation with the functions of the photographic practices and to examine some transgressive contemporary aesthetics described in the novel and linked to the general strategy of manipulation developed by the artist Zeus-Peter Lama. The growing media visibility of the representations and the depersonalization of the model, reduced to the state of an object of visual consumption, bring the man-piece-of-art to the dimension of a spectacular sensation.Transformed into an “uncanny” work of art and launched as a product on the art market, Tazio discovers and describes various art movements, performances and artists from the paradoxical viewpoint of a living work of art. His depiction of the multiplicity of transgressive aesthetics is ironical and satirical; the references and allusions to different works of art and phenomena in the art world from the second half of the 20th century reflect the excesses generated in search of creative innovations.
Keywords: Éric-Emmanuel Schmitt; contemporary novel; photography; art; manipulation